2017
DOI: 10.17221/144/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total phenolic content and antioxidant activity of malting and hulless barley grain and malt extracts

Abstract: AbstractŠimić G., Horvat D., Dvojković K., Abičić I., Viljevac Vuletić M., Tucak M., Lalić A. (2017): Evaluation of total phenolic content and antioxidant activity of malting and hulless barley grain and malt extracts. Czech J. Food Sci., 35: 73-78.Nine malting and six hulless barley varieties were evaluated for their grain characteristics, β-glucans, total phenolic contents, and corresponding antioxidant activities determined by DPPH radical scavenging method. Samples were malted to compare malt quality prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…TPCs were lowest in seeds (98.45, 109.06, and 127.40 mg/100 g DM in corn, wheat, and barley, respectively) ( Figure 2a). These TPC levels are consistent with previous studies in corn [23,24] , wheat [19,24,25] , and barley [24,26] seeds. Figure 2a shows TPC levels in seeds and the sprouts and grasses at different days.…”
Section: Tpc Quantification In Seeds Sprouts and Grassessupporting
confidence: 93%
See 1 more Smart Citation
“…TPCs were lowest in seeds (98.45, 109.06, and 127.40 mg/100 g DM in corn, wheat, and barley, respectively) ( Figure 2a). These TPC levels are consistent with previous studies in corn [23,24] , wheat [19,24,25] , and barley [24,26] seeds. Figure 2a shows TPC levels in seeds and the sprouts and grasses at different days.…”
Section: Tpc Quantification In Seeds Sprouts and Grassessupporting
confidence: 93%
“…This is possibly due to the higher antioxidant potential of hydrolyzed bound phenolics present in sprouts. [26,32,44] TPCs in sprouts are the sum of soluble phenolics in seed, bio-synthesized phenolics and hydrolyzed phenolics present as bound in the cell walls. [7,45]…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Similar results regarding Kolbach index values were described by Krstanović et al [7] (2015), where the values of the Kolbach index reached 41% in the modified malting process. In a previous study published by Šimić et al [28], there were also reported differences in malting behavior between hull-less and hulled varieties. Results obtained for the friability, difference in extract yield between finely and coarsely ground malt, wort viscosity and Kolbach index revealed that malting varieties achieved better cytolytic and proteolytic modification than hull-less barley lines.…”
Section: Resultsmentioning
confidence: 76%
“…In a study conducted by Krstanović et al [7], a narrow connection between β-glucan content and viscosity was determined, meaning that lower β-glucan content in hull-less barley reduces the viscosity of wort. Hull-less barley is known to have a higher β-glucan content [28] and thus increased viscosity values, which are considered problematic during filtration in the brewing process. Viscosity values are approximately 1.4-1.5 times higher for hull-less barley, with the exception for 2016 where viscosity was 2.5 times higher than in hulled varieties.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ABTS radical scavenging absorbance was taken at 734 nm using the same apparatus. The extract of BMG was evaluated by the modified method of Simic et al [ 28 ]. Briefly, 1 mL of a 0.5 mmol/L methanol solution (of DPPH) and 2 mL of methanol were added to each extract (0.2 mL).…”
Section: Methodsmentioning
confidence: 99%